The Effect of Breakfast Habits on Learning Concentration Among First Semester Students of The Faculty of Psychology and Health UIN Sunan Ampel Surabaya - Ghani, Hendryanto Maulana; Widayanti, Linda Prasetyaning; Suprayogi, Dedy (International Conference on Sustainable Health Promotion, 2025)
Breakfast is an essential activity that supports energy availability and cognitive functions, particularly students’ learning concentration. However, breakfast is often neglected due to time constraints and a lack of awareness regarding the importance of morning nutrition. This study aims to examine the effect of breakfast habits on the learning concentration of first semester students at the Faculty of Psychology and Health, UIN Sunan Ampel Surabaya. The method used was quantitative research with a cross-sectional design involving 74 respondents, determined through simple random sampling. The research instrument was an online questionnaire that had been tested for validity and reliability. Data were analyzed using the Independent Sample T-Test to determine differences in concentration based on breakfast habits. The results showed a significant difference between students who regularly had breakfast and those who did not, with a p-value of 0.020. The average concentration score of students who had breakfast was 34.97, higher than those who did not, with a score of 32.70. This study concludes that breakfast has a significant effect on students’ learning concentration and should be promoted as part of a healthy lifestyle to support academic success.